Early adjuvant radiotherapy in the treatment of atypical meningioma. (June 2016) - Jenkinson, Michael D.; Waqar, Mueez; Farah, Jibril Osman; Farrell, Michael; Barbagallo, Giuseppe M.V.; McManus, Robin; Looby, Seamus; Hussey, Deirdre; Fitzpatrick, David; Certo, Francesco; Javadpour, Mohsen
Highlights: Atypical meningioma are prone to recurrence. The role of adjuvant radiotherapy has not been defined. Extent of resection influences time to meningioma recurrence. In this retrospective series radiotherapy did not reduce meningioma recurrence. An international prospective randomised controlled trial (ROAM) is planned. Abstract: Atypical meningiomas have a greater propensity to recur than benign meningiomas and the benefits of early adjuvant radiotherapy are unclear. Existing studies report conflicting results. This retrospective cohort study evaluated the role of early adjuvant radiotherapy following surgical resection of atypical meningioma. A triple center case-note review of adults with newly-diagnosed atypical meningiomas between 2001 and 2010 was performed. Pathology diagnosis was made according to the World Health Organization classification in use at the time of surgery. Patients with multiple meningiomas, neurofibromatosis type 2 and radiation-induced meningiomas were excluded. Extent of resection was defined as gross total resection (GTR; Simpson Grade I–III) or subtotal resection (STR; Simpson Grade IV–V). Survival analysis was performed using the Kaplan–Meier method. One hundred thirty-three patients were identified with a median age of 62 years (range 22–86 years) and median follow-up of 57.4 months (range 0.1–152.2 months). Tumors were mostly located in the convexity (50.4%) or falcine/parasagittal regions (27.1%). GTR (achieved in 85%) was associated with longer progression free survival (PFS) (5 year PFS 81.2% versus 40.08%, log-rank = 11.117, p  = 0.001) but not overall survival (OS) (5 year OS 76.6% versus 39.7%, log-rank = 3.652, p  = 0.056). Following GTR, early adjuvant radiotherapy was administered to 28.3% of patients and did not influence OS (5 year OS 77.0% versus 75.7%, log-rank = 0.075, p  = 0.784) or PFS (5 year PFS 82.0% versus 79.3%, log-rank = 0.059, p  = 0.808). Although extent of resection emerged as an important prognostic variable, early adjuvant radiotherapy did not influence outcome following GTR of atypical meningiomas. Prospective randomized controlled trials are planned.